2022
DOI: 10.3390/ijms231810402
|View full text |Cite
|
Sign up to set email alerts
|

Truxene-Centered Electron Acceptors for Non-Fullerene Solar Cells: Alkyl Chain and Branched Arm Engineering

Abstract: A series of symmetrical truxene-centered and 3-ethylrhodanine end-capped electron acceptors with high absorption coefficient, namely Tr(Hex)6-3RD, Tr(Dec)6-3RD, and Tr(Hex)6-6RD, were prepared and constructed for non-fullerene solar cells. To satisfy solution-processability, multiple energy levels, and suitable morphology, these three acceptors were comparatively studied through alkyl chain (hexyl/decyl) and branched-arm engineering (three/six branched arms). The six-bladed propeller acceptor of Tr(Hex)6-6RD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Lin et al [6] reported on the synthesis of novel oligomers capable of functioning as nonfullerene acceptors for OSCs. Several systems with the organic moiety truxene at the center, endcapped with 3-ethylrhodanine, as electron acceptors for OSCs with high absorption coefficients, were prepared and tested.…”
mentioning
confidence: 99%
“…Lin et al [6] reported on the synthesis of novel oligomers capable of functioning as nonfullerene acceptors for OSCs. Several systems with the organic moiety truxene at the center, endcapped with 3-ethylrhodanine, as electron acceptors for OSCs with high absorption coefficients, were prepared and tested.…”
mentioning
confidence: 99%